Effects of Confounding Factors on Liver Stiffness in Two-Dimensional Shear Wave Elastography in Beagle Dogs - Cha, Jinwoo; Kim, Jayon; Ko, Jaeeun; Kim, Jaehwan; Eom, Kidong (Frontiers in Veterinary Science, 2022)
Two-dimensional shear wave elastography (2D-SWE) is a powerful technique that can non-invasively measure liver stiffness to assess hepatic fibrosis. This study aimed to identify the effects of confounding factors, including anesthesia, breathing, and scanning approach, on liver stiffness when performing 2D-SWE in dogs. Nine healthy Beagle dogs were included in this study. Hepatic 2D-SWE was performed, and liver stiffness was compared between conscious and anesthetized states, free-breathing and breath-holding conditions, and intercostal and subcostal approaches. For the anesthetized state, the breath-holding condition was subdivided into seven phases, which included forced-expiration (5 and 10 mL/kg), end-expiration (0 cm H2O), and forced-inspiration (5, 10, 15, and 20 cm H2O), and liver stiffness was compared among these phases. Changes in liver stiffness were compared between intercostal and subcostal approaches according to breathing phases. No significant difference was observed in liver stiffness between the conscious and anesthetized states or between the free-breathing and beath-holding conditions. No significant difference was noted in liver stiffness among the breathing phases, except for forced-inspiration with high airway pressure (15 and 20 cm H2O in the intercostal approach and 10, 15, and 20 cm H2O in the subcostal approach), which was associated with significantly higher liver stiffness (p < 0.05). Liver stiffness was significantly higher in the subcostal approach than in the intercostal approach (p < 0.05). Changes in liver stiffness were significantly higher in the subcostal approach than in the intercostal approach in all forced-inspiratory phases (p < 0.05). In conclusion, when performing 2D-SWE in dogs, liver stiffness is unaffected by anesthesia and free-breathing. To avoid inadvertent increases in liver stiffness, the deep inspiratory phase and subcostal approach are not recommended. Thus, liver stiffness should be interpreted considering these confounding factors.